Edipeni dan Adiluhung Proyeksi Filsafati dalam Pertunjukan Wayang - Suyanto Suyanto (Institut Seni Indonesia Surakarta, 2022)
This essay is entitled “Edipeni Dan Adiluhung: Proyeksi Filsafati Dalam Pertunjukan Wayang” (Edipeni and Adiluhung: Proyection of Philosophy in Wayang Performance). The main point is to discuss how far the wayang performance has phylosophical values. It is very important because during the global era, cross culture between Western and Eastern have seriously effect toward the quallity and morallity of Indonesian young generation.Wayang performance seem to be a symbol of human life which has more spiritual than physical values. For the society who like it, it would be used as a reference for the role of action and character buillding, and the values of wayang performance look as a way of life, ideolgy, also as an esence of human life. In wayang performance, there would be found the role of the corellation between human and God, human and human, also human and nature. Beautifullness of wayang performance include the whole values which is exposed in performance. So the meaning of phylosophy in wayang really has a large meaning.